2012
DOI: 10.1021/la3036677
|View full text |Cite
|
Sign up to set email alerts
|

Human Serum Albumin Monolayers on Mica: Electrokinetic Characteristics

Abstract: Adsorption of human serum albumin (HSA) on mica from 0.15 M NaCl solutions and various pH values was studied using in situ streaming potential measurements, AFM imaging, and XPS. The results obtained by the streaming potential were consistent with AFM measurements and theoretical predictions based on the random sequential adsorption model. This allowed one to determine both the kinetics of adsorption and the maximum coverage of HSA as a function of pH. At pH 3.5, the maximum coverage of HSA was 0.45 (which cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 54 publications
4
34
0
Order By: Relevance
“…It has been shown by various theoretical calculations performed using the chemical composition of proteins that the surface charge of the molecule is heterogeneously distributed in the form of positive and negative patches, existing over a wide range of pH. This hypothesis is supported by analogous results reported in the literature on proteins: HSA 43 , IgG 44 , brinogen 45 , NT-4 34 and lysozyme 46 .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It has been shown by various theoretical calculations performed using the chemical composition of proteins that the surface charge of the molecule is heterogeneously distributed in the form of positive and negative patches, existing over a wide range of pH. This hypothesis is supported by analogous results reported in the literature on proteins: HSA 43 , IgG 44 , brinogen 45 , NT-4 34 and lysozyme 46 .…”
Section: Discussionsupporting
confidence: 59%
“…We carried out BDNF adsorption at PAMAM dendrimers in high ionic strength (0.15M) solution, because the reduction of the repulsive interactions between the protein and polymers has been previously reported for different proteins, including polyclonal rabbit immunoglobulin (IgG) 47 , brinogen 45 , albumin 43 and NT-4 34 . By applying this approach, we obtained higher adsorbed amount of BDNF which makes our nanocarriers more biocompatible.…”
Section: Discussionmentioning
confidence: 99%
“…Major assumption in our calculations was that particles were irreversibly adsorbed on the static lattice surface with a very high force as our experimental observations imply (adsorption isotherms in Figure ), as well as many studies suggest such a behavior . Adsorbed particles were assumed to form a monolayer over the lattice surface, as was observed for human SA adsorption on hydrophilic mica surfaces, and not to diffuse laterally among adjacent binding sites. The total amount of BSA particles, including both adsorbed and diffusing in the simulation box, was kept fixed during the simulations to mimic experimental conditions.…”
Section: Methodsmentioning
confidence: 63%
“…Zeta potential of bare and HSA covered mica was determined via streaming potential measurements using a parallel-plate cell described in previous works [13,14].…”
Section: Methodsmentioning
confidence: 99%
“…Basic physicochemical characteristics of HSA such as the diffusion coefficient, hydrodynamic diameter, electrophoretic mobility as a function of pH and ionic strength have been determined in previous works [11][12][13][14]. It was shown that at pH 5.2 the electrophoretic mobility of the protein vanishes independently of ionic strength, therefore, this pH is defined as the isoelectric point.…”
Section: Introductionmentioning
confidence: 99%